GENETIC PARAMETERS, CHARACTER ASSOCIATION AND PATH COEFFICIENT ANALYSIS IN POST-RAINY SORGHUM LANDRACES - P. RAJENDRA KUMAR; D. SAIDA NAIK, A. ANISHA, V. HEMALATHA, R. MADHUSUDHANA (The Journal of Research, PJTSAU, 2023)
Field experiment involving 97 post-rainy (rabi) sorghum landraces was conducted at the Indian Institute of Millets Research (ICAR-IIMR), Hyderabad (Telangana) during 2020-21 to estimate genetic parameters, character association and path coefficients for grain yield, its component traits, and other agronomic traits. Significant variation between genotypes was noticed for all the 12 traits studied. Estimates of heritability varied from 25% (number secondary branches on central primary branch of panicle) to 94% (panicle length). Grain yield per plant, test weight, panicle weight, panicle length and number of grains on central primary branch of panicle have shown high estimates of heritability and genetic advance. Genotypic correlation analysis of grain yield showed positive significant association with all the traits except number of grains on central primary branch of panicle. Panicle weight and number of grains per panicle are strongly correlated with grain yield genotypically. Further, path coefficient analysis revealed that test weight, plant height, panicle weight, and seed hardness were the traits showing positive direct effect on grain yield at both phenotypic and genotypic level. CSV-216R (114g), Malegaon local (104g), CSV-29R (97g), IC345199 (92g) are the genotypes which yielded highest among all the genotypes in terms of grain yield per plant. Selection of tall plants with more green leaves and medium length panicles holding a greater number of primary branches with bold seeds could be fetching for improvement of grain yield in post-rainy sorghum.